Тренінгові технології як засіб розвитку емоційного інтелекту - Гура, Тетяна Віталіївна (Національний технічний університет "Харківський політехнічний інститут", 2022)
В публікації висвітлено поняття емоційний інтелект як здатності точно сприймати, оцінювати і виражати емоції. Особлива увага приділена аналізу тренінгу як формі активного навчання, метою якого є формування лідерського потенціалу майбутніх фахівців ЗВТО. В статті висвітлені основні принципи та методи тренінгової роботи, зокрема розглянуто тренінгову технологію для розвитку емоційного інтелекту. Під час констатувального етапу педагогічного експерименту доведено необхідність розробки тренінгу для розвитку емоційного інтелекту для студентів технічного університету. Висвітлено особливості застосування тренінгових технологій під час формувального експерименту в експериментальній групі. В статті доведено ефективність застосування тренінгових технологій в ЗВТО для розвитку оемоційного інтелекту – основної складової лідерського потенціалу.

The concept of emotional intelligence as the ability to accurately perceive, evaluate and express emotions is highlighted in the publication. Particular attention is paid to the analysis of training as a form of active learning, which aims to build leadership potential in future HITE specialists. The basic principles and methods of training are highlighted in the article. Special attention is paid to training technology for the development of emotional intelligence. The need to develop training for the development of emotional intelligence in students of technical universities is proved in the article during the statement stage of the pedagogical experiment. The article reveals the peculiarities of the application of training technologies during the formative experiment in the experimental group. The effectiveness of training technologies in HITE for the development of emotional intelligence, that is the main component of leadership potential, is proved in the article.
Training technologies as a means of emotional intelligence development
Keywords: тренінг; технологія; завклад вищої освіти; технічний університет; training; technology; institution of higher education; technical university